Propuesta para la redistribución de planta de la empresa Ficol s.a.s de la ciudad de Barranquilla. (2022)
Currently, during the flow of processes, bottlenecks have been created in companies as a result of the obstacles that have been encountered due to poor plant distribution, these organizations are beginning to look for alternatives that are viable to solve these problems. For the company Ficol S.A.S. of the city of Barranquilla, I consider making a diagnosis of its own plant distribution, being able to look at the delays that are presented in the current processes, with this diagnosis it will be possible to detect opportunities for improvement of the current plant distribution, allowing to improve the flow of materials, cost reduction with the current space available for current processes. Ficol S.A.S. By submitting to these suggested changes in the plant redistribution, you will have to make a minimal economic investment, compared to an expansion of the current plant infrastructure. In other words, so that these expectations can be met, the current management of the company Ficol S.A.S. I authorize the investigation in your company, where four objectives were established which aim to solve the problem you have thanks to the Analysis of the Systematic Approach of Plant Distribution (S.L.P.).